Intercanine and Intermolar Widths in Class I, II And III Malocclusions (Journal of Nobel Medical College, 2025)
Background: Transverse malocclusions are quite common in almost all population. Abnormal intermolar and intercanine width results in transverse malocclusions.Materials and Methods: Study models of 83 orthodontic patients attending orthodontic department of Nobel Medical College Teaching Hospital from 2021 Jan to 2024 Sep were segregated according to Angle’s classification of malocclusion. The intercanine and intermolar widths were assessed on the dental casts. The data were subsequently analyzed using SPSS version 20. A one-way ANOVA analysis was conducted to compare the intercanine and intermolar widths across the five malocclusion groups.Results: The mean intercanine width of maxilla among all types of malocclusions is 24.837 mm whereas it is 18.172 mm in mandible. Similarly, the mean intermolar width of maxilla is 33.973mm and 29.771mm in mandible among all types of malocclusions. There was no any statistically significant difference in intermolar and intercanine width of both maxilla and mandible among different 5 types of malocclusion groups.Conclusion: Class I malocclusion had maximum maxillary and mandibular intermolar width whereas Class III maloclussion had minimum maxillary and mandibular intermolar width. However, no significant difference was present in the intercanine and intermolar width among the different malocclusion groups.